Comparison of Material Properties of Duplex Stainless Steel 1.4462 Processed by DED-LB/M and PBF-LB/M - Maier, Andreas; Rühr, Manuel; Stephan, Marcel; Roth, Stephan; Schmidt, Michael (Additive Manufacturing in Multidisciplinary Cooperation and Production, 2023)
Duplex stainless steels (DSS) combine high strength and ductility with excellent corrosion resistance due to a synergistic effect between ferritic and austenitic phases in a balanced ratio. In Additive Manufacturing (AM) processes such as Laser-based Directed Energy Deposition (DED-LB/M) and Laser Powder Bed Fusion (PBF-LB/M), it is a great challenge to achieve high build quality and the desired duplex microstructure at the same time. In this work, the as-built (AB) and subsequent heat-treated (HT) conditions of DSS 1.4462 were compared in terms of microstructural and mechanical properties after being processed by both DED-LB/M and PBF-LB/M. DED-LB/M resulted in a heterogeneous microstructure with an almost balanced ferrite–austenite phase ratio. Strength and ductility of the DED-LB/M AB condition correspond to the specification of conventionally manufactured DSS 1.4462 by reaching 468 ± 1 MPa in yield strength (YS) and 31 ± 1% elongation at break (A). A standard post-process heat treatment consisting of solution annealing (1,050 °C; 2 h) and quenching in water homogenized the DED-LB/M microstructure but had only a minor effect on the mechanical properties. In contrast to DED-LB/M, PBF-LB/M leads to a finer-grained and mainly ferritic microstructure (14 - 17% austenite). Ductility (A = 15 ± 1%) and impact toughness (KV = 48 ± 12 J) of the PBF-LB/M AB condition are very low due to the lack of austenite formation. Consequently, post-process heat treatment was required to achieve the desired ferrite–austenite phase balance. The subsequent equalization of the phase ratio reduced the overall hardness and strength (YS = 720 ± 1%), but significantly increased ductility (A = 39 ± 1%) and impact toughness (KV = 125 ± 15 J), resulting in mechanical properties that were in good agreement with the specification of DSS 1.446
Keywords: directed energy deposition; laser powder bed fusion; duplex stainless steel; microstructure; mechanical properties